Strategies to sustain a quality improvement initiative in neonatal resuscitation - Carlien van Heerden; Carin Maree; Elsie S. Janse van Rensburg (AOSIS, 2016)
Background: Many neonatal deaths can be prevented globally through effective resuscitation. South Africa (SA) committed towards attaining the Millennium Development Goal 4 (MDG4) set by the World Health Organization (WHO). However, SA's district hospitals have the highest early neonatal mortality rates. Modifiable and avoidable causes associated with patient-related, administrative and health care provider factors contribute to neonatal mortality. A quality improvement initiative in neonatal resuscitation could contribute towards decreasing neonatal mortality, thereby contributing towards the attainment of the MDG4. Aim: The aim of this study was, (1) to explore and describe the existing situation regarding neonatal resuscitation in a district hospital, (2) to develop strategies to sustain a neonatal resuscitation quality improvement initiative and (3) to decrease neonatal mortality. Changes that occurred and the sustainability of strategies were evaluated. Setting: A maternity section of a district hospital in South Africa. Methods: The National Health Service (NHS) Sustainability Model formed the theoretical framework for the study. The Problem Resolving Action Research model was applied and the study was conducted in three cycles. Purposive sampling was used for the quantitative and qualitative aspects of data collection. Data was analysed accordingly. Results: The findings indicated that the strategies formulated and implemented to address factors related to neonatal resuscitation (training, equipment and stock, staff shortages, staff attitude, neonatal transport and protocols) had probable sustainability and contributed towards a reduction in neonatal mortality in the setting. Conclusion: These strategies had the probability of sustainability and could potentially improve neonatal outcomes and reduce neonatal mortality to contribute toward South Africa's drive to attain the MDG4.